Researches of system water of food raw materials by thermodynamic and molecular-kinetic methods - Погожих, Микола Іванович; Пак, Андрій Олегович; Чеканов, Микола Анатолійович; Іштван, Єгор Олексійович; Павлюк, Ігор Миколайович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper deals with developing views on the humidity of food raw materials and products from them that allow to predict and scientifically justify functional and technological role of a particular component of food raw materials or product in terms of its interaction with water. It is noted that despite the variety of humidity research methods and plenty of information, obtained using them, the content of the concepts of “free” and “bound” water is not clear enough, their role in the material, absolute and relative content is not investigated fully and accurately. The aim of the research was to obtain new scientific data about the condition and structure of water in various food products and raw materials, depending on their processing technologies; define correlation between the results of studies of humidity in food raw materials and products, obtained by different thermodynamic and molecular-kinetic methods. Within the main concept of the paper, the notion of “system water” was introduced, and expediency of calculating molar concentrations for the food system components was justified. Using different thermodynamic and molecular-kinetic methods, system water of different food raw materials and products was investigated. The patterns of changes in the condition and structure of water in food raw materials and products, occurring in their processing were determined by compiling information on the water condition and structure during interaction with the components that make up food raw materials and products. It is noted that the research results and obtained patterns for the system water of food raw materials and products allow to visualize the processes of humidity change under different external factors.